(untitled) (Latakia University Journal -Medical Sciences Series, 2024)
Introduction:The incidence of hip fractures and associated deaths among the elderly has increased in recent years, with 1.3 million cases reported worldwide in 1990, and this number is expected to reach 21-7 million in 2050. Due to the functional disability and financial burden these fractures cause on the individual and society, their prediction is of great importance. Objective: The study was conducted to evaluate vitamin D and parathyroid hormone levels in predicting the occurrence of hip fractures among the elderly at Tishreen University Hospital in Lattakia during the period between February 2022 and January 2024. Materials and methods: The research sample included 58 patients admitted to the Orthopedic Surgery Department at Tishreen University Hospital in Lattakia, aged 50-90 years, and diagnosed with a hip fracture during the period between February 2022 and January 2024. The control sample included 30 patients who visited the emergency department or were admitted to the Orthopedic Surgery Department for reasons other than hip fractures.All study patients were subjected to a medical history, patient information, clinical examination and laboratory evaluation upon admission to the orthopedic department, which included biochemical parameters including calcium and phosphate, in addition to other blood tests. Patients were divided into groups according to the type of hip fracture. The study sample consisted of 31 patients with femoral neck fracture, 27 patients with intertrochanteric fracture, and 30 controls. Vitamin D and parathyroid hormone levels were measured, in addition to all biochemical parameters including calcium and phosphate, for patients upon admission to the department. Results: The mean values ​​of vitamin D were lower in the hip fracture group with p-value=0.0001, and the mean values ​​of parathyroid hormone were higher in the hip fracture group with p-value=0.0001, while blood calcium was lower in the hip fracture group with p-value=0.001. We also found a relationship between age and vitamin D, which was lower in the older age group (70-90 years), in addition to a statistical relationship with parathyroid hormone, which was higher in that group. Finally, a relationship was observed between the type of hip fracture and both vitamin D and parathyroid hormone levels, as we found that in patients diagnosed with femoral neck fractures, vitamin D values ​​were lower with a decrease in parathyroid hormone values, while in patients diagnosed with intertrochanteric fractures, vitamin D values ​​were lower with an increase in parathyroid hormone values. Conclusions: Vitamin D and parathyroid hormone levels in elderly people over 50 years of age are considered the most important parameters for predicting the risk of hip fractures.